Children are sociologists - E. Chen, Eva; H. Corriveau, Kathleen; L. Harris, Paul (Anales de Psicología / Annals of Psychology, 2011)
Recent research has established that young children are quite sensitive to the characteristics of individual informants. They prefer to seek and endorse information from informants with whom they are already familiar or from informants who have proven reliable in the past. We report an elaboration of this line of research in which children‟s sensitivity to an informant‟s group status is probed. A consistent finding across various procedures is that when preschool children are presented with conflicting claims, one claim made by two or three people and another made by a single person, they agree with the majority. This form of endorsement is especially apparent when members of the majority belong to the same racial group as the child rather than a different racial group. Moreover, this bias toward the majority is extended to individual members of the majority. For example, when children are presented with conflicting claims by two informants, one who previously belonged to the majority and one who did not, they are inclined to endorse the member of the majority. By implication, young children are astute sociologists. They take careful note of the relationships among individuals, particularly relationships of agreement or disagreement.